2012
DOI: 10.1111/j.1365-2567.2011.03548.x
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of the candidate rheumatoid arthritis autoantigen aggrecan by antigen‐specific B cells induces enhanced CD4+ T helper type 1 subset differentiation

Abstract: Summary Effective immune responses require antigen uptake by antigen‐presenting cells (APC), followed by controlled endocytic proteolysis resulting in the generation of antigen‐derived peptide fragments that associate with intracellular MHC class II molecules. The resultant peptide–MHC class II complexes then move to the APC surface where they activate CD4+ T cells. Dendritic cells (DC), macrophages and B cells act as efficient APC. In many settings, including the T helper type 1 (Th1) ‐dependent, proteoglycan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 70 publications
2
21
0
Order By: Relevance
“…In order to study B‐cell APC function in RA, we have recently generated B cells expressing BCR specific for aggrecan (A20‐agg). These cells present soluble aggrecan extremely efficiently, requiring approximately 10 000‐fold lower levels of antigen than that required by non‐specific B cells . In the present study we demonstrate that these aggrecan‐specific B cells also acquire, in a contact‐dependent manner, ECM‐immobilized aggrecan leading to the activation of CD4 + T cells specific for the immunodominant G1, p84‐103 CD4 + T‐cell epitope.…”
Section: Introductionmentioning
confidence: 55%
“…In order to study B‐cell APC function in RA, we have recently generated B cells expressing BCR specific for aggrecan (A20‐agg). These cells present soluble aggrecan extremely efficiently, requiring approximately 10 000‐fold lower levels of antigen than that required by non‐specific B cells . In the present study we demonstrate that these aggrecan‐specific B cells also acquire, in a contact‐dependent manner, ECM‐immobilized aggrecan leading to the activation of CD4 + T cells specific for the immunodominant G1, p84‐103 CD4 + T‐cell epitope.…”
Section: Introductionmentioning
confidence: 55%
“…The frequencies of IL-17-and IFN-γ-secreting CD4 + T cells expressing the clonotypic TCR were, however, significantly lower in B cell-deficient TS1(SW)xHACII mice that failed to develop disease, which is notable since anti-IL-17R treatment of TS1(SW)xHACII mice was also able to prevent arthritis development. B cells have previously been shown to support the formation of antigen-specific effector CD4 + T cells in response to both foreign antigens and autoantigens, including studies in an antigen-induced model of inflammatory arthritis (2125). Accordingly, B cells appear to promote arthritis development in TS1(SW)xHACII mice at least in part through their ability to support the development of Th17 cells expressing the clonotypic TCR, which accumulated in higher numbers in the joint-draining LNs of arthritic TS1(SW)xHACII mice than was the case for either IFN-γ-secreting CD4 + T cells in TS1(SW)xHACII mice, or IL-17-secreting CD4 + T cells in TS1xHACII mice.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, studies evaluating anti-B cell agents (such as rituximab) have demonstrated efficacy in some patients (1618). Anti-B cell therapy might affect arthritis development by reducing the levels of arthritogenic autoantibodies (1619), but B cells can also act as an APC population for effector CD4 + T cells (2025). Whether B cells can play an important role in supporting CD4 + T cell differentiation in inflammatory arthritis is not well understood (2325).…”
Section: Introductionmentioning
confidence: 99%
“…Citrullinated arthritogenic aggrecan peptide has been considered to be a biomarker of RA, having been identified in the peripheral blood of RA patients, and has shown to stimulate a specific CD4 response [38][39][40]. It is considered a candidate autoantigen for RA, being one of the principle proteoglycans for cartilage extracellular matrix functioning in cushioning synovial joints, self-antigens that share a common sequence at position 70-74 of the human leucocyte antigen Drelated (HLA-DR) b-chain in 90% of RA patients [38,41]. In RA patients, stimulation with the arthritogenic aggrecan peptide resulted in a strong and significant expansion of Th9 cells.…”
Section: Il-9 and Th9 Cells In Ramentioning
confidence: 99%